A comprehensive literature review of juvenile programs, policies, and monitoring systems - Herter, Jason (2016)
This paper investigates past literature on juvenile-based programs, policies, and monitoring systems. It shows what strides practitioners have taken to reduce recidivism and how programs have tried to limit past failures. By showing what has worked and what has failed, we can develop future research and designs, measure the effects of different theories, and even add more important categories to future programs. This research presents information that may assist practitioners who work directly with juveniles and those who are involved in researching and developing future juvenile programs and policies